LENGHT-WEIGHT RELASTIONSHIP AND CONDITION FACTOR OF Brachirus Orientalis (Bloch &Schneider, 1801) IN IRAQ MARINE WATER - Layla A. Aufi (University of Thi-Qar Journal of agricultural research, 2022)
Length-weight relationships of Brachirus Orientalis, in coastal areas of Faw, south of Iraq was carried out on January to December 2019. Total length were ranged from 15.3 to 42 cm for 193 collected specimens, weight ranging from 59.60 to 1123.65g. According to the length-weight correlations the b value was 3.021. This demonstrated that positive allometric growth for both sexes. Calculated values of condition factor were 1.02and 1.12 for male, female respectively that showed healthy condition of fish.Key words: Brachirus Orientalis, Length-weight relationships, condition factor, Iraq marine water.